Pengaruh Penggunaan Media Benang terhadap Hasil Menggambar Perspektif Siswa Kelas VII SMP Methodist Kabanjahe - Ameta Ulasia Ginting; Nelson Tarigan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to determine the effect of using thread media on students’ perspective drawing result. The population in this study were all the works of class VII students of junior high school Methodist Kabanjahe totaling 180 works from 90 students. Sampling using cluster random sampling technique, obtained a research sample, namely class VII-MATIUS, two stages of action were given, namely initial sampling with the teaching-learning process using image media. Then after that the second sampling was carried out with the teaching and learning process using thread media. Data collection methods used include documentation, observation and testing methods. This research is a quantitative research design with a quasi-experimental research design (Quasi-Experimental Design). Based on the results of the study, the first test score average was 81,37 and the second test score was 89,29. The results of the mean difference test show that the average of the second value is better than the first value. Based on the results of hypothesiss testing with a significance of α=0,5 with dk 58 obtained < = 1,9811. So the results of the hypothesis testing obtained tcount 5,72 >ttable1,9811. So Ho is accepted as well as rejected by Ha, then the conclusion is that there is an influence between the use of thread media on learning outcomes of perspective drawing in VII grade students of junior high school Methodist Kabanjahe.